Height, age at menarche, body weight and body mass index in life-long vegetarians - Rosell, M; Appleby, P; Key, T (Cambridge University Press, 2005)
Objective: We investigated whether life-long adherence to a vegetarian diet is associated with adult height, age at menarche, adult body weight and body mass index (BMI), used as indicators of growth, development and obesity, in a large sample of adults. Design: This was a cross-sectional study. Anthropometric data and information on age, ethnicity, education, age at menarche and age at becoming a vegetarian were obtained through a questionnaire. Self-reported height and weight were calibrated using predictive equations derived from a previous validation study. Setting: United Kingdom. Subjects: The study includes 45962 British men and women aged ≥ 20 years of whom 16083 were vegetarians (not eating fish or meat). Reslts: In men and women, there were no significant differences in height, weight or BMI between life-long vegetarians (n=125 (men) and n=265 (women) and people who became vegetarian at age ≥ 20 years (n=3122 (men) and n=8137 (women)). Nor was there a significant difference in age at menarche between life-long vegetarian women and women who became vegetarian at age ≥ 20 years. Conclusion: This stidy suggests that, compared with people who become vegetarian when adult, life-long vegetarians do not differ in adult height, weight, BMI or age at menarch in women.